Development of RP-HPLC methods for the Estimation of Cefixime in Bulk Drugs and in Pharmaceutical Dosage Forms - Gowri Sankar, D.; Raju, M.S.M.; Kalyan Sumanth, S.; Pawar, A.K.M. (Asian Journal of Chemistry, 2016)
Two simple and sensitive reverse phase high performance liquid chromatographic methods (A and B) have been developed for the estimation of cefixime in bulk form and in pharmaceutical formulations. The quantification was carried out using a RP silica column and RP C18 column in isocratic mode for methods A and B respectively. The mobile phase was made up of acetonitrile and water in the ratio of 3 : 2 (v/v). Beclomethasone dipropionate was used as an internal standard. The detection was carried out at 254 nm and the linearity was found to be in the range of 3–15 μg/mL. The methods were duly validated by evaluation of the required parameters.